The effect of ground poppy seeds with different properties on the rheological properties of white chocolate - Zay Katalin (Élelmiszervizsgálati közlemények, 2018)
In the coarse of our research, white chocolate samples prepared using poppy seeds and poppy seed flour of different grain size and in different amounts were compared in order to be able to determine what kind of effect they had on the rheological properties of the finished products, i.e., how the penetration and rotational viscosity properties of the finished products were influenced. Based on the results of rotational viscometry, there was a significant difference between the samples that contained poppy seeds, depending on the poppy seed grain size. However, on the basis of the penetration measurement results, there was a significant difference between the samples containing lower oil content poppy seed flour, correlating to the grain size. During grinding, two opposite effects occur: on the one hand, removal of the oil content, and on the other hand, an increase in the number of particles in a given volume unit. In the technology, these two effects prevail together, but to varying degrees. There was a significant difference in the average particle size of the paste samples containing poppy seeds or poppy seed flour. Based on the results obtained using main component analysis and discriminant analysis it can be said that the main factor when classifying chocolates containing poppy seeds/poppy seed flour was the form of the poppy seeds/poppy seed flour added to the chocolate. The effect of the amount of the added poppy seeds/poppy seed flour was only secondary. Based on the results of the consumer sensory evaluation, samples that contained whole poppy seeds in smaller amounts were most preferred by the consumers interviewed, while chocolates that contained larger amounts of whole poppy seed flour were less preferred.